-3x+4(2x+2)=3(5x-3)+7

Simple and best practice solution for -3x+4(2x+2)=3(5x-3)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+4(2x+2)=3(5x-3)+7 equation:


Simplifying
-3x + 4(2x + 2) = 3(5x + -3) + 7

Reorder the terms:
-3x + 4(2 + 2x) = 3(5x + -3) + 7
-3x + (2 * 4 + 2x * 4) = 3(5x + -3) + 7
-3x + (8 + 8x) = 3(5x + -3) + 7

Reorder the terms:
8 + -3x + 8x = 3(5x + -3) + 7

Combine like terms: -3x + 8x = 5x
8 + 5x = 3(5x + -3) + 7

Reorder the terms:
8 + 5x = 3(-3 + 5x) + 7
8 + 5x = (-3 * 3 + 5x * 3) + 7
8 + 5x = (-9 + 15x) + 7

Reorder the terms:
8 + 5x = -9 + 7 + 15x

Combine like terms: -9 + 7 = -2
8 + 5x = -2 + 15x

Solving
8 + 5x = -2 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
8 + 5x + -15x = -2 + 15x + -15x

Combine like terms: 5x + -15x = -10x
8 + -10x = -2 + 15x + -15x

Combine like terms: 15x + -15x = 0
8 + -10x = -2 + 0
8 + -10x = -2

Add '-8' to each side of the equation.
8 + -8 + -10x = -2 + -8

Combine like terms: 8 + -8 = 0
0 + -10x = -2 + -8
-10x = -2 + -8

Combine like terms: -2 + -8 = -10
-10x = -10

Divide each side by '-10'.
x = 1

Simplifying
x = 1

See similar equations:

| X-10+2x+40=90 | | -x/2=5 | | 7r^2+16r-15=0 | | 5x+4=90 | | .5y+4=0.1428y | | 41-(3x+12)=3(x+5)+x | | 6x+12-4x=48 | | .5n=-8.3 | | x+163+38=2x+125 | | d/5=7 | | 2x^2+6x^2+6x=6x+40 | | 5n^2+34n-48=0 | | 5n^2+34-48=0 | | 9x^2+12+3=0 | | 3(4x^2-6x-7)=0 | | 10*54p= | | 4=0.4(3d-5-5) | | 43y=16 | | 2a^2-13a-7=0 | | 13(t+4)=2(t-10)-27 | | 2(4x+5)=-19+13 | | 4=0.4(3x-5-5) | | 11z/16+7z/8=5/15 | | 35=8x+138 | | .625j=-10 | | 6(y-8)-y=2(-9-y) | | x+x-40=90 | | 4(2t+2)-9=2 | | 19x-5=13x-35 | | p-18=-29 | | 6-6x=-3x-6 | | x+.75=2x-.75 |

Equations solver categories